KONSEPSI PRASADA DI PURA TAMAN AYUN MENGWI, BADUNG - Ni Gusti Ayu Nyoman Budiasih (Jurnal Kajian dan Terapan Pariwisata, 2020)
The conception of ”Prasada” is a place of worship of ancestral spirits, but at Prasada in Taman Ayun Temple in Mengwi is not as usual, but has its own uniqueness. Generally the conception of Prasada as a place of worship for ancestral spirits, but this Prasada serves as a place of worship of the “Mountain God” for fertility, this can be strenghened from the name of the Prasada namely “Prasada Cili Gading”. Cili means “Sri” be identified as Sri Goddess with the Her Sakti Vihsnu Goddess, which symbolizes fertility, and Gading means “Yellow” be identified as ‘Rice’ colored yellow. This Prasada also called “Lingga” worship of the Shiva Goddess as symbol of victory from I Gusti Agung Putu which is considered successful in upholding prosperity and protect his people, and established the Kingdom of Mengwi. The worship of “Mountain Gods” is the symbolic concept of “Mount Mangu”, as the essence of the balance of the universe which symbolizes fertility, prosperity, and happiness, the natural is maintained, sustainable, balanced, for the life. Besides also functions as a “Glory Symbol” of victory, this Prasada functions as a place of worship for the “Shiva Parwata”. If true, this Prasada also functions to worship “Shiva Vishnu” Goddess in an aspect known as “Harihara Goddess”. Prasada Cili Gading, the form is just like as Prasada but does not function as the true concept of Prasada. The architectural of this Prasada indeed shows the type of East Java temple which is slim, is classified as the 17th Century periodization.